Recombinant amyloid beta-peptide production by coexpression with an affibody ligand. - Macao, Bertil; Hoyer, Wolfgang; Sandberg, Anders; Brorsson, Ann-Christin; Dobson, Christopher M; Härd, Torleif (BMC Biotechnology, 2008)
BACKGROUND: Oligomeric and fibrillar aggregates of the amyloid beta-peptide (Abeta) have been implicated in the pathogenesis of Alzheimer's disease (AD). The characterization of Abeta assemblies is essential for the elucidation of the mechanisms of Abeta neurotoxicity, but requires large quantities of pure peptide. Here we describe a novel approach to the recombinant production of Abeta. The method is based on the coexpression of the affibody protein ZAbeta3, a selected affinity ligand derived from the Z domain three-helix bundle scaffold. ZAbeta3 binds to the amyloidogenic central and C-terminal part of Abeta with nanomolar affinity and consequently inhibits aggregation. RESULTS: Coexpression of ZAbeta3 affords the overexpression of both major Abeta isoforms, Abeta(1-40) and Abeta(1-42), yielding 4 or 3 mg, respectively, of pure 15N-labeled peptide per liter of culture. The method does not rely on a protein-fusion or -tag and thus does not require a cleavage reaction. The purified peptides were characterized by NMR, circular dichroism, SDS-PAGE and size exclusion chromatography, and their aggregation propensities were assessed by thioflavin T fluorescence and electron microscopy. The data coincide with those reported previously for monomeric, largely unstructured Abeta. ZAbeta3 coexpression moreover permits the recombinant production of Abeta(1-42) carrying the Arctic (E22G) mutation, which causes early onset familial AD. Abeta(1-42)E22G is obtained in predominantly monomeric form and suitable, e.g., for NMR studies. CONCLUSION: The coexpression of an engineered aggregation-inhibiting binding protein offers a novel route to the recombinant production of amyloidogenic Abeta peptides that can be advantageously employed to study the molecular basis of AD. The presented expression system is the first for which expression and purification of the aggregation-prone Arctic variant (E22G) of Abeta(1-42) is reported. Original Publication: Bertil Macao, Wolfgang Hoyer, Anders Sandberg, Ann-Christin Brorsson, Christopher ...